2 HUBUNGAN PERILAKU DIET DENGAN KADAR GULA DARAH PADA PENDERITA DIABETES MELITUS TIPE II - Purwandari, Henny; Setyobudi, Moch Khamim (Judika (Jurnal Nusantara Medika), 2016)
Background Type II diabetes mellitus is a chronic disease that is not curable but it is very potential to be prevented and controlled through diet. The bad behavior of diet resultedin blood sugar levels remain high and facilitate the emergence of bernagai complications. Thepurpose of this study was to determine the relationship of diet behavior with blood sugarlevels in patients with diabetes mellitus type II Jogomerto In the village district of TanjungAnom. Methods This study research design correlation with retrospective approach, which washeld on 12 May 2015. The population was all patients with diabetes mellitus type IIJogomerto In the village district of Tanjung Anom number of 18 respondents by totalsampling. Variable independent research that dietary behavior, while the dependent variableof research that blood sugar levels. Data were analyzed with statistical test Spearman Rankby SPSS 20 For Windows with α = 0.05. Result Results of this study show quite as much as the behavior of 14 respondents(77.8%) and poor blood sugar levels as much as 13 respondents (72.2%). Statistical testresults obtained using Spearman rank ρ value = 0.018 ≤ α = 0.05 means Ha accepted thatthere is a relationship between dietary behavior with blood sugar levels of people withdiabetes mellitus type II in the village of the district of Tanjung Anom Jogomerto. With thevalue of r = 0.562 or level of relationship is. Conclusion The food we eat will affect blood sugar levels in the body, so theuncontrolled behavior of food consumption or poor diet behavior will result in high bloodsugar levels and facilitate the emergence of a variety of complications.Keyword : Behavior diet, blood sugar levels, diabetes mellitus type II